Correlation of Selected Anthropometric Characteristics of Infants: A Forensic Perspective in North Central Nigeria - O., Mosugu O.; N., Okolo S. (Darul Yasin Al Sys, 2025)
Accurate anthropometric data on infants are critical for forensic investigations involving newborns and young children, particularly in cases related to child identification, welfare, and criminal inquiries. Despite the relevance of such data, there remains a significant gap in forensic anthropometric records for infants in Nigeria. This study aims to address this gap by examining the interrelationships among key anthropometric parameters of infants and exploring their potential forensic applications. A cross-sectional design was employed to collect anthropometric measurements from 570 infants in Jos, Plateau State, Nigeria. Data collection adhered to established ethical protocols, and statistical analysis was performed using the Number Cruncher Statistical System (NCSS/PASS 2019, version 19.0.2, Dawson Edition, USA). Results revealed strong, positive correlations among infant weight, age, mid-upper arm circumference, crown-heel length, foot length, hand length, and head circumference. These findings underscore the consistency and reliability of these parameters in reflecting infant growth patterns and physical development. The study contributes valuable baseline data for forensic science in Nigeria and demonstrates how infant anthropometry can support investigative processes involving missing children, age estimation, and identification in legal or humanitarian contexts. The implications of this research are significant for improving forensic capacity in pediatric and child protection cases, particularly within resource-limited settings.